PENDIDIKAN ISLAM SEBAGAI SEBUAH SISTEM DI ERA 4.0 - Triana Rosalina Noor (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
The era of 4.0 has brought changes in the order of human life from the order of behavior to the organization. And education can be a solution to these fundamental changes. However, Islamic education that is intended to be implemented should be a well-systemized Islamic education. This is because Islamic education will not only build people in the competencies of religious knowledge but also religious knowledge all of which come from the Koran. Through well-organized Islamic education, it will help shape the personality of the students in a comprehensive personality growth, have good intellectuals and optimal faith. Therefore, it is appropriate to change towards era 4.0, Islamic education is required to be more sensitive to the symptoms of social change in society. Islamic education should properly improve and beautify itself so that it can not only be able to do the best innovations so that it is always contextual to demands and changes. Islamic education begins to strengthen the components that are in it so that the quality and end products produced are a superior generation for the era.